2020
DOI: 10.3390/ijms21186556
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib and other CML Tyrosine Kinase Inhibitors in Thrombosis

Abstract: Abl1 kinase has important biological roles. The Bcr-Abl1 fusion protein creates undesired kinase activity and is pathogenic in 95% of chronic myeloid leukemia (CML) and 30% of acute lymphoblastic leukemia (ALL) patients. Targeted therapies to these diseases are tyrosine kinase inhibitors. The extent of a tyrosine kinase inhibitor’s targets determines the degree of biologic effects of the agent that may influence the well-being of the patient. This fact is especially true with tyrosine kinase inhibitor effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 108 publications
2
25
0
Order By: Relevance
“…In addition to BCR-ABL1, CML TKIs have distinct inhibitory activities to other kinases and the differences in substrate spectrum might contribute to their various cardiovascular toxicities. Previous studies reveal that SRC kinase and FGFRs are common targets for ponatinib, dasatinib and bosutinib but they are not inhibited by imatinib and nilotinib (Moslehi and Deininger, 2015;Rossari et al, 2018;Zeng and Schmaier, 2020;Lee et al, 2021) which is consistent with our observation that ponatinib, dasatinib, bosutinib but not imatinib and nilotinib induce dorsal aorta stenosis in zebrafish (Figure 1B), so we hypothesized that inhibition of SRC or FGFRs is involved in the vasculopathies of CML TKIs. We investigated this hypothesis by testing the effect of SRC inhibitor (Src-IN-1) or FGFR inhibitor (infigratinib) on vessel integrity.…”
Section: Src Inhibition Contributes To Vascular Toxicity Of CML Tkissupporting
confidence: 92%
See 2 more Smart Citations
“…In addition to BCR-ABL1, CML TKIs have distinct inhibitory activities to other kinases and the differences in substrate spectrum might contribute to their various cardiovascular toxicities. Previous studies reveal that SRC kinase and FGFRs are common targets for ponatinib, dasatinib and bosutinib but they are not inhibited by imatinib and nilotinib (Moslehi and Deininger, 2015;Rossari et al, 2018;Zeng and Schmaier, 2020;Lee et al, 2021) which is consistent with our observation that ponatinib, dasatinib, bosutinib but not imatinib and nilotinib induce dorsal aorta stenosis in zebrafish (Figure 1B), so we hypothesized that inhibition of SRC or FGFRs is involved in the vasculopathies of CML TKIs. We investigated this hypothesis by testing the effect of SRC inhibitor (Src-IN-1) or FGFR inhibitor (infigratinib) on vessel integrity.…”
Section: Src Inhibition Contributes To Vascular Toxicity Of CML Tkissupporting
confidence: 92%
“…Inhibition of VEGF receptor signaling is well known to induce vasculopathies, however, it might not be the cause of CML TKI induced vessel defects. Bosutinib inhibits VEGFRs but it does not demonstrate vascular toxicity in patients while the vascular toxic dasatinib does not inhibit VEGFRs ( Moslehi and Deininger, 2015 ; Zeng and Schmaier, 2020 ; Lee et al, 2021 ). We revealed that inhibition of SRC contributes to vascular toxicity as combinatory inhibition of ABL1 and SRC is sufficient to induce vessel constriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ponatinib can inhibit not only PDGFR and SRC family kinases but also KDR (VEGFR) and FGFR activities, and ponatinib has been associated with a higher frequency of hypertension, AOEs, and venous thromboembolism (VTE), rather than fluid retention or effusions [60]. VEGFR is expressed in vascular endothelial cells and hematopoietic cells, mediating angiogenesis and vascular permeability as well as bone metabolism, hematopoiesis, wound healing, and development [61].…”
Section: Specific Targets Of Tyrosine Kinase Inhibitors and Related Adverse Eventsmentioning
confidence: 99%
“…The introduction of tyrosine kinase inhibitors (TKIs) for the treatment of CML changed the natural history of this disease [ 1 ], but these drugs are also associated with some short- and long-term toxicities. Cardiovascular (CVS) complications are increasingly reported with the use of certain TKIs, such as ponatinib and nilotinib [ 1 , 2 , 3 ]. The reasons underlying these associations are not fully understood and are a matter of ongoing research, but several factors can be implicated, including TKI effect on the endothelium, on inflammatory pathways and on pro-thrombotic properties of the various blood cells [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%